The complete chloroplast genome of Tulipa gesneriana (Liliaceae) and its phylogenetic analysis. Issue 7 (3rd July 2022) - Yuan, Lingli; Yan, Xiaozhi; Chen, Xian; Zhu, Xingfu
Abstract: The complete chloroplast genome sequence of Tulipa gesneriana L. was determined to investigate its phylogenetic position. This plastome is 151, 958 base pairs (bp) in length, and comprises two inverted repeat (IRa and IRb) regions of 26, 352 bp, a small single-copy region of 17, 123 bp and a large single-copy region of 82, 131 bp. The GC contents of the cp genome were 36.6%. In total, we annotated 126 genes including 81 protein-coding genes, 37 tRNA genes, and eight rRNA genes. Phylogenetic analysis based on nine chloroplast genomes indicates that T. gesneriana is closely related to T. iliensis and T. thianschanica .